PENGARUH KOMPENSASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. HADJI KALLA CABANG PALU - TAMPING, NURRAHMI UTAMI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
The purpose of this study is to analyze and determine the effect of employee compensation, motivation and work discipline variables on PT. Hadji Kalla Branch Palu. The population used in this study is 46 respondents, the entire population is made as respondents (census). Data analysis method used in this research is multiple linear regression method using the help of SPSS for Windows Relase 20.0 program. Hypothesis testing used has a significance level of ? = 0.05. The test results obtained that simultaneously compensation, motivation and work discipline affect performance, with the regression equation of Y = ? + b1X1 + b2X2 + b3X3 or Y = 2,338 + 0,718 (X1) + 0,164 (X2) + 0,162 (X3) and with the level The coefficient of determination (R2) is 0.679 or 67.9% while the remaining 32.1% is influenced by other variables not observed in this study. Partially with the standard obtained the results of research X1, X2 and X3 have an effect on Y with a significance value of X1 of 0.00, X2 of 0.03 and X3 of 0.00.